2014
DOI: 10.1007/s10753-014-9834-0
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone Dampens Pulmonary Inflammation in a Porcine Model of Acute Lung Injury

Abstract: The hallmarks of acute lung injury (ALI) are the compromised alveolar-capillary barrier and the extravasation of leukocytes into the alveolar space. Given the fact that the peroxisome proliferator-activated receptor-γ agonist rosiglitazone holds significant anti-inflammatory properties, we aimed to evaluate whether rosiglitazone could dampen these hallmarks of local pulmonary inflammation in a porcine model of lung injury. For this purpose, we used a model of lipopolysaccharide (LPS, 50 μg/kg)-induced ALI. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Rosiglitazone belongs to the thiazolidinedione class of PPARγ agonists and is a potent antidiabetic agent. Ongoing research regarding its role in suppressing inflammation 11 , inducing apoptosis and suppressing tumor growth 12 in parallel to inhibiting TGFβ1 signaling 8 , makes it a good therapeutic candidate for IPF patients. Since rosiglitazone might not be the ideal therapeutic option for patients who are at risk of developing ischemic heart disease 13 , exploring the applicability of alternative therapeutic compounds is clinically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Rosiglitazone belongs to the thiazolidinedione class of PPARγ agonists and is a potent antidiabetic agent. Ongoing research regarding its role in suppressing inflammation 11 , inducing apoptosis and suppressing tumor growth 12 in parallel to inhibiting TGFβ1 signaling 8 , makes it a good therapeutic candidate for IPF patients. Since rosiglitazone might not be the ideal therapeutic option for patients who are at risk of developing ischemic heart disease 13 , exploring the applicability of alternative therapeutic compounds is clinically relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated notable guiding roles for netrin‐1 and its receptors in organogenesis, angiogenesis, and tumorigenesis . Recently, netrin‐1 was shown to play a key role in controlling leukocyte traffic in peripheral organs during acute inflammation . With an acute inflammatory response complete resolution of tissue inflammation is the ideal outcome for the affected tissues to reinstitute their functional integrity.…”
mentioning
confidence: 99%
“…(19) Recently, netrin-1 was shown to play a key role in controlling leukocyte traffic in peripheral organs during acute inflammation. (14,20,21) With an acute inflammatory response complete resolution of tissue inflammation is the ideal outcome for the affected tissues to reinstitute their functional integrity. In this context, homeostasis is achieved by limiting the further infiltration of polymorphonuclear cells (PMNs) and promoting the local phagocytosis of cellular debris and/ or invading organisms (22) orchestrated by local chemical mediators such as specialized proresolving lipid mediators (SPMs).…”
mentioning
confidence: 99%
“…In the LPS-induced acute porcine lung injury model, 78 intravenous rosiglitazone significantly controlled local pulmonary inflammation as reflected by a significant reduction in the expression of cytokines and neutrophil activity within the alveolar compartments. 162 Other studies have demonstrated that when rosiglitazone is used after or before exposure to the aerosolized LPS insult, which induces neutrophilia and associated survival factors/chemoattractants such as CC chemokine ligand-5 (CCL5) and granulocyte colony-stimulating factor (G-CSF) in the airways, it inhibits airway inflammation. [163][164][165][166] In addition, several lines of evidence have found that rosiglitazone achieves its antiinflammatory effects through the upregulation of HO-1 expression.…”
Section: Ppar-γ Agonists: Rosiglitazonementioning
confidence: 99%